2015
DOI: 10.1089/apc.2015.0014
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to HIV Pre-Exposure Prophylaxis (PrEP) from Non-Occupational Post-Exposure Prophylaxis (nPEP) in a Comprehensive HIV Prevention Clinic: A Prospective Cohort Study

Abstract: The uptake of pre-exposure prophylaxis (PrEP) for HIV prevention remains low. We hypothesized that a high proportion of patients presenting for HIV non-occupational post-exposure prophylaxis (nPEP) would be candidates for PrEP based on current CDC guidelines. Outcomes from a comprehensive HIV Prevention Clinic are described. We evaluated all patients who attended the HIV Prevention Clinic for nPEP between January 1, 2013 and September 30, 2014. Each patient was evaluated for PrEP candidacy based on current CDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Other studies among MSM have also found higher risk sexual behaviours (such as condomless sex) to be associated with hypothetical interest in using PrEP [28,29,35], as well as actual uptake in open-label studies [20,21]. Other characteristics independently associated with willingness to use PrEP in our study included higher perceived HIV risk and prior use of PEP, the latter finding highlighting the potential to transition individuals from PEP to PrEP [39,40]. Further work is needed to better understand the relative preferences regarding the use of new HIV prevention technologies among MSM, for instance, by using discrete choice experiments [41,42].…”
Section: Discussionsupporting
confidence: 64%
“…Other studies among MSM have also found higher risk sexual behaviours (such as condomless sex) to be associated with hypothetical interest in using PrEP [28,29,35], as well as actual uptake in open-label studies [20,21]. Other characteristics independently associated with willingness to use PrEP in our study included higher perceived HIV risk and prior use of PEP, the latter finding highlighting the potential to transition individuals from PEP to PrEP [39,40]. Further work is needed to better understand the relative preferences regarding the use of new HIV prevention technologies among MSM, for instance, by using discrete choice experiments [41,42].…”
Section: Discussionsupporting
confidence: 64%
“…[5][6][7] Additionally, those individuals diagnosed with bacterial STIs in nPEP settings may be good candidates for HIV pre-exposure prophylaxis (PrEP). 8,9 This study provides evidence that such screening is valuable and that practitioners should be vigilant about investigating for these potentially transmissible infections.…”
Section: Discussionmentioning
confidence: 78%
“…Second, the cohort was highly educated, and we restricted analyses to MSM, limiting our ability to draw conclusions about other groups. However, this sample does reflect the population typically seen for nPEP in our setting,[ 56 , 57 ] and likely reflects the success of awareness-raising efforts in MSM communities. Of note, people who used nPEP in the context of sexual assault were unlikely included in this sample, since these patients are usually seen at sexual assault centres separate from our hospitals.…”
Section: Discussionmentioning
confidence: 97%